Market Focus, New Products, and Entrepreneurship Improve UMKM Performance in Gempol: Fokus Pasar, Produk Baru, dan Kewirausahaan Meningkatkan Kinerja UMKM di Gempol - Zahro, Fatimatuh; Sari, Dewi Komala (Indonesian Journal of Innovation Studies, 2025)
General background The vital role of Micro, Small, and Medium Enterprises (MSMEs) in boosting national economic resilience underscores the need for effective marketing strategies. Specific background In Gempol, Pasuruan, a high concentration of convection MSMEs leads to intense market competition, demanding a thorough understanding of performance drivers. Knowledge gap Previous academic literature provides inconsistent evidence regarding the collective relationships between market orientation, product innovation, and entrepreneurial orientation on marketing performance. Aims This study sought to ascertain the simultaneous influence of market orientation, product innovation, and entrepreneurial orientation on the marketing performance of MSMEs in Gempol. Results Utilizing a quantitative approach on 100 randomly sampled MSMEs and analyzed using Smart PLS-4, the findings confirmed that market orientation, product innovation, and entrepreneurial orientation each positively influence marketing performance. Novelty This research provides empirical evidence specifically from the context of Indonesian convection MSMEs using a robust path analysis model. Implications The findings strongly suggest that MSMEs should prioritize these three orientations to maintain a competitive advantage, thereby ensuring sustained increases in sales and profitability. Highlights: Market focus, product novelty, and risk-taking drive MSME performance. A quantitative survey was conducted on 100 randomly sampled MSMEs in Gempol. Smart PLS-4 confirmed the simultaneous positive influence of all three variables. Keywords: Market Orientation, Product Innovation, Entrepreneurial Orientation, Marketing Performance, MSMEs